The Existence of Quranic Exegesis Learning in Javanese Pesantren - Supriyanto (Indonesian Journal of Islamic Literature and Muslim Society, 2022)
In the current digital era, learning models are continuously undergoing rapid changes and developments, marked by the emergence of various strategies, methods, and diverse learning approaches. However, amid these advancements, the traditional learning model in Javanese pesantren persists to this day. One enduring model is Quranic learning. This article aims to explore the sustainability and relevance of the Quranic learning model in Javanese Pesantren, which remains integral to Islamic education in Indonesia. The research methodology employed is descriptive qualitative, utilizing data derived from interviews and observations conducted at al-Balagh Pesantren in East Java. The findings of this research reveal that the Quranic learning model in Islamic boarding schools possesses unique and distinctive characteristics, placing a primary emphasis on Quranic studies. The sorogan and bandongan learning methods are two commonly employed approaches in Javanese Pesantren. These methods significantly impact the learning process within these boarding schools, particularly in reinforcing students' comprehension of the subject matter and fostering social interaction skills, as well as establishing connections with teachers and peers.